Strength and dynamic balance performance in soccer players in the United States: age, sex, and bilateral differences - Zhanxin Sha; Boyi Dai; Boyi Dai (Frontiers in Sports and Active Living)
Quantification of asymmetries between the two limbs is informative in assessing the risk of injury and performance deficits, but there is a paucity of studies investigating the effects of age and sex on bilateral asymmetry in young soccer players. This cross-sectional study aimed to investigate the effects of age and sex on strength and dynamic balance in 7- to 24-year-old soccer players in the United States. A total of 174 young soccer players participated in the study (Age 7–9 years: 26 females and 16 males; Age 10–12 years: 32 females and 31 males; Age 13–17 years: 17 females and 25 males; Age >18 years: 13 females and 14 males). Jump displacement, peak force, and asymmetry during countermovement jump with arm swing and landing, peak force and asymmetry during push-up, and normalized reaching distances for upper and lower extremity reaching tests were quantified. Preferred legs and arms were defined as the preferred kicking leg or throwing arm. As age increased, both preferred and non-preferred sides demonstrated decreased landing forces, increased jump displacement, and increased normalized peak forces during push-ups in both males and females (p < 0.05). Males showed greater jump displacement, normalized landing forces, and normalized peak forces in push-ups compared to females in several age groups (p < 0.05). No significant differences were observed for asymmetry variables between ages or sexes, and on average, most bilateral asymmetry variables were less than 5%. Age was associated with strength but not dynamic balance performance in healthy soccer players in the United States. Male and female players demonstrated similar changes, and bilateral asymmetries were on average small. Soccer players may need more dynamic balance training over time as they progress to higher levels of competition. Landing technique training may be implemented for young soccer players to decrease the high impact landing forces and landing related injury risk. Asymmetries and their relationships with injury risk should be evaluated on an individual basis, as their relationships with age and sex were weak. Future longitudinal and cohort studies are warranted to further elucidate the relationship among strength, dynamic balance, and injury risk in soccer players.